The Effect of Work Stress on Employee Performance CV. Neureus Putra District. Subang - Bagas Satria Putra; Anggi Pasca Arnu (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to examine the effect of job stress on employee performance in the press division at CV. Neureus Putra Kab. Subang using quantitative methods. The research used descriptive analysis techniques and SEM PLS analysis with primary data sources in the form of questionnaires distributed to 102 employees of the press division of CV. Neureus Putra. The results show that the partial effect between job stress on employee performance is -0.157 or -16%. Which means that job stress has a negative significant effect effect on employee performance.